(untitled) (Journal of Creative Industry and Sustainable Culture, 2023)
Culture is a manifestation of real behaviour created by humans as cultured social beings. Culture is a form of actualization of art that exists in a collection of people. There are seven elements of universal cultures, one of them is art. Traditional art is a means that is used to create a sense of beauty from within the human soul, one of which is to be expressed on a beauty of cloth. Gedhok cloth is a traditional textile which uses two production techniques, namely weaving to produce the textured motif on cloth, then coloring the cloth with batiktechnique to produce another set of motifs. The purpose of this research is to document the history of gedhog cloth which is part of a culture in society that is starting to recede so that it can be one way to preserve the culture of gedhog cloth throughscientific writing. The research uses descriptive analysis using historical diachronic approach. The existence of gedhok weaving is sustain due to continuous support from its community which still adheres to the teachings of their ancestors.